2016
DOI: 10.1016/j.gca.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectroscopic study of organic phosphate esters coprecipitated with calcite

Abstract: Organic phosphorus incorporated in calcite during laboratory precipitation experiments and in natural cave deposits was investigated by solid-state NMR spectroscopy. For calcite precipitated in the presence of organic phosphoesters of varying size and functionality, solid-state 31 P{ 1 H} CP/MAS NMR shows that the phosphoesters were incorporated intact into the solid. Systematic changes in the 31 P NMR chemical shift of the phosphate group were observed between the solid phosphoester and that incorporated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 88 publications
(115 reference statements)
4
7
0
Order By: Relevance
“…Through the competitive reaction between two hydroxyl groups, PU-gp was successfully fabricated and characterized using 31 P NMR (Figure b). The peak was shifted from the zero point of standard phosphoric acid to 6.68 ppm, indicating the presence of the phosphate monoester (R-O-PO­(OH) 2 ) of glycerol phosphates, whereas no peaks were detected in pure PU, as this compound has no P source or linkage …”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Through the competitive reaction between two hydroxyl groups, PU-gp was successfully fabricated and characterized using 31 P NMR (Figure b). The peak was shifted from the zero point of standard phosphoric acid to 6.68 ppm, indicating the presence of the phosphate monoester (R-O-PO­(OH) 2 ) of glycerol phosphates, whereas no peaks were detected in pure PU, as this compound has no P source or linkage …”
Section: Results and Discussionmentioning
confidence: 98%
“…The peak was shifted from the zero point of standard phosphoric acid to 6.68 ppm, indicating the presence of the phosphate monoester (R-O-PO(OH) 2 ) of glycerol phosphates, whereas no peaks were detected in pure PU, as this compound has no P source or linkage. 22 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboxyl groups (COOH -) are common in natural DOM, and can readily be adsorbed onto calcite, which has a net positive charge (via Ca 2+ ). By contrast, an NMR (Nuclear Magnetic Resonance) spectroscopy study revealed that small organic (P containing) molecules can be incorporated in the calcite structure, thus supporting the notion that speleothems may provide a resilient record of organic matter present during crystallisation (Phillips et al, 2016). These results implied that calcite precipitated under natural conditions can accommodate organic molecules as structural defects.…”
Section: Dom Incorporation Mechanisms and Partition Coefficientsmentioning
confidence: 85%
“…The presented 1 H/ 31 P REDOR results are indicative of hydrogen phosphate groups (12–15 ppm Figure 1d) and water molecules (peak at 7 ppm). This broad 31 P peak exhibits a strong 13 C/ 31 P REDOR dephasing effect, indicating atomically close proximity to multiple carbonate groups (Phillips et al., 2016). The NMR spectroscopic results from the synthetic calcite samples indicate that calcite‐hosted phosphate accounts for the majority form of phosphate in these samples, thus, the features observed in the XANES spectroscopy of these synthetic calcite samples can be used to fingerprint calcite‐hosted phosphate in geological samples.…”
Section: Discussionmentioning
confidence: 99%